ASSESSEMENT OF SELF-EAR CLEANING PRACTICES, AWARENESS, AND ASSOCIATED EAR HEALTH OUTCOMES: A SCOPING REVIEW - Ochin Ngozika Georginia; Gideon Aduk Amuga; Akyala Ishaku Adamu; Ochin Chiedoziem Anthony; Abah Michael Idoko (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
Self-ear cleaning, the practice of manually removing earwax or debris from the ear canal using objects such as cotton buds, matchsticks, or hairpins is a widespread global behaviour driven predominantly by hygiene misconceptions. Despite well-documented risks including tympanic membrane perforation, earwax impaction, external auditory canal injury, and otitis externa, self-ear cleaning remains prevalent across diverse populations worldwide. No comprehensive scoping review has mapped the global evidence on the prevalence, motivations, tools, awareness, and ear health outcomes of self-ear cleaning across adult and paediatric populations. To systematically map and synthesise available evidence on the prevalence of self-ear cleaning practices, the tools and motivations involved, community awareness and knowledge levels, and the associated ear health outcomes, with a view to identifying evidence gaps and informing future primary research and public health education. This scoping review followed the Arksey and O’Malley framework and the Joanna Briggs Institute (JBI) scoping review methodology, and is reported in accordance with the PRISMA Extension for Scoping Reviews (PRISMA-ScR). A systematic search was conducted in PubMed/MEDLINE, Scopus, Web of Science, CINAHL, and Google Scholar for studies published between January 2000 and March 2025. Studies of any design reporting on self-ear cleaning practices, awareness, motivations, tools, or health outcomes were eligible. Two reviewers independently screened titles, abstracts, and full texts. Data were charted and synthesised thematically. Thirty-one studies involving 14,218 participants across 14 countries were included. Self-ear cleaning prevalence ranged from 67.8% to 98% across settings, with cotton buds the predominant tool (range: 51.7%–85.1%). The most common motivations were removal of perceived dirt (earwax), relief from itching, and cosmetic concerns. Community awareness of the ear’s natural self-cleaning mechanism was consistently low across all populations. Reported ear health complications included otitis externa (6–28.3%), earwax impaction (8.9–22%), tympanic membrane perforation (1.5–6.5%), and external auditory canal injury (up to 32.4%). Healthcare worker knowledge of ear hygiene risks was poor in most settings, with only 10.7% demonstrating adequate knowledge in one Nigerian study. Video-oto-endoscopy was identified as an underutilised but superior diagnostic modality for objective documentation of ear canal and tympanic membrane pathology associated with self-cleaning. Self-ear cleaning is a high-prevalence, globally distributed behaviour with significant ear health consequences, rooted in persistent misconceptions about earwax and hygiene. Evidence gaps exist on objective clinical documentation using video-oto-endoscopy, behavioural determinant analysis using theoretical frameworks, and targeted health education intervention effectiveness. These gaps represent priorities for future primary research. Urgent, culturally appropriate public health messaging is needed to promote safe ear hygiene across all demographic groups.